Base pressure at supersonic speeds in the presence of a supersonic jet - Craven, A. H.; Chester, D. H.; Graham, B. H. (College of Aeronautics, 1960)
The effects on base pressure of jet Mach number, free stream Reynolds number and jet to base diameter ratio have been investigated experimentally. It was found that, for jet stagnation pressures greater than that required for the nozzle to reach its design Mach number, an increase of jet Mach number reduced the base pressure. Similarly the base pressure increased with increase of the ratio of jet diameter to base diameter and, at nigh jet stagnation pressures, base pressures higher than free stream static pressure were found. The base pressurewas independent of frek: stream Reynolds numbers greater than 2 x 10[to the power of 6] per foot but increased with reduction of Reynolds number below 2 x 10[to the power of 6] per foot. Unsteady wave patterns were found when the jet Mach number did not differ markedly from the free stream Mach number and the jet had just reached its design conditions.